Research on the Quality Evaluation of Chinese Government Websites : Based on Government Websites in 98 Provinces and Municipal Cities - Zhu, Yongdi (My University, 2024)
Government websites play a crucial role in China's digital governance, digital government construction, and the modernization of national governance systems and capabilities. They receive strong support from the Party-state government, both environmentally and politically. The trend of reform, public demand, and policy orientation have led to rapid development of government information disclosure and government websites. In various regions, there has been some progress in the levels of government information disclosure and administrative service. However, due to differences in regional development and levels of informatization, government websites still face challenges such as insufficient transparency of information and uneven levels of administrative services. Therefore, it is necessary to clarify the evaluation indicators for government websites from various perspectives, incorporate them into the evaluation content, and propose targeted paths for improving the quality of government websites. Firstly, this thesis analyzes the relationship between the government and the public to summarize the relevant elements of the government website quality evaluation system, including service provider elements, service target elements, and service content elements, corresponding to the two main subjects of government and the public, and the government information and services as the object of contact. Based on the two main subjects of government and the public, evaluation dimensions related to government website quality are extracted, corresponding to the SERVQUAL theory, and used as primary evaluation indicators. Then, based on the explanation of each dimension in the SERVQUAL theory and evaluation indicators in other literature, the secondary evaluation indicators of government website quality are summarized. Finally, a comprehensive government website quality evaluation indicator system is formed by integrating these indicators. This evaluation indicator system includes 6 primary indicators and 32 secondary indicators. Next, this thesis utilizes a Back Propagation(BP) Neural Network model to establish a government website quality evaluation model, focusing on local government websites that provide open data platforms. Based on the relevant government website data collected for the year 2021, the model evaluates the quality of government websites in 2022. The evaluation and analysis results include a comparison of the overall quality of all government websites and the quality of government websites in representative regions. Finally, based on the evaluation results and analysis conclusions, three targeted strategies for improving government website quality are proposed: in-depth assessment result application to enhance the competence of civil servants, innovative service awareness to deepen government information utilization, and solidifying grassroots website service capabilities with a focus on advancing indicator optimization.
Keywords: Government websites, Quality evaluation, SERVQUAL Model, BP neural network